96 Setting Up Your Office and Practice: Exclusively Hair Transplants versus Combined Practice (Hair Transplantation, 2023)
This chapter cannot outline all the details necessary to succeed as a hair surgeon. Instead, the objective is to focus on some of the most important principles necessary to create a successful and sustainable hair restoration practice. First, the physician must be exposed to the field enough and mentored appropriately to gain a deep passion for hair surgery, for without it success will be elusive. Second, a lifelong commitment to education gained through reading textbooks and journals, attending conferences, observing, and sharing with esteemed colleagues will help strengthen the foundation for current and ongoing success. Third, ethical hair surgery in which the surgeon is in command of the procedure rather than in a position of merely delegating the procedures to technicians. Fourth, this chapter covers leadership, which is a critical element to establishing a strong office culture that in turn facilitates a profitable practice. Finally, the heart of the chapter delves into the mechanics of how to successfully combine hair surgery with either an existing cosmetic practice or vice versa, or alternatively running a practice dedicated exclusively to hair surgery.
Keywords: setting up practice; combined practice; leadership; ethics; passion; education; marketing; referrals; internet